2020
DOI: 10.1186/s12879-020-05153-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of infective endocarditis in a tertiary hospital in China from 2007 to 2016

Abstract: Background: To explore the trends in epidemiology and the risk factors related to the prognosis of infective endocarditis in a tertiary hospital over the past ten years. Methods: A retrospective cohort study was performed. A total of 407 consecutive patients who were admitted with infective endocarditis were included. The clinical characteristics and the risk factors related to the prognosis of infective endocarditis during this period were analyzed. Results: A total of 407 patients with infective endocarditis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
7
18
1
2
Order By: Relevance
“…Consistent with previous studies we found that CHD was a common factor associated with IE in children, being present in 36% of paediatric IE cases [ 2 , 20 , 21 , 22 , 23 ]. In contrast, CHD related IE made up only 1.2% of all adult IE cases.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies we found that CHD was a common factor associated with IE in children, being present in 36% of paediatric IE cases [ 2 , 20 , 21 , 22 , 23 ]. In contrast, CHD related IE made up only 1.2% of all adult IE cases.…”
Section: Discussionsupporting
confidence: 92%
“… 2 In Hong Kong, the incidence of IE remained stable in the past two decades, which is in line with studies from other regions and previous Asian studies carried out in China. 4 , 6 , 10 , 24 , 25 For example, a previous North American study reported a stable trend incidence of 7.8 per 100,000 person-year in 2013. 6 A recent Scottish study also identified a static incidence with a rate of 8.1 per 100,000 person-year in 2014.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 4 , 5 , 6 Previous studies performed in Asia were either from a single centre or did not comprehensively assess changes in incidence, demographics, and outcomes. 8 , 9 , 10 , 11 , 12 The temporal changes in incidence, patient characteristics, and related mortality of IE, remain unknown in the Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…Endocarditis is a severe infectious disease with a high mortality rate [ 2 - 5 ]. Its in-hospital mortality rates are 12-17%, 23%-26%, 10%, and 8% for inherent valve, prosthetic valve, cardiac implantable electronic device, and right-sided endocarditis, respectively [ 6 ]. Fungal endocarditis in patients with prostatic valves can be a severe threat with high mortality and morbidity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%